Pengaruh Bauran Pemasaran terhadap Pengalaman Pasien Rawat Inap di Rumah Sakit Permata Hati Kecamatan Mandau Tahun 2022 - Tengku Widya Tri Handayani; Budi Hartono; Zainal Abidin; Ennimay Ennimay; Ahmad Satria Efendi (Universitas Batanghari Jambi, 2022)
Hospitals have a very strategic role in an effort to accelerate the improvement of public health status. The new paradigm of health care requires hospitals to provide quality services according to the needs and desires of patients. The marketing mix can be used as a marketing tool that makes it easier for hospitals to achieve their marketing goals. The purpose of this study was to determine the effect of the marketing mix on the experience of inpatients at Permata Hati Hospital, Mandau District in 2022. This type of research was descriptive quantitative using a cross sectional design. This study reveals that the marketing mix affects patient practice with the most dominant variable affecting patient experience is the process variable.